Some Characteristics of Abstracts in Scientific Research Papers in French - Mirić, Milica M. (Collection of Papers of the Faculty of Philosophy in Priština, 2025)
Scientific communication, governed by clearly defined formal, linguistic, and content-related rules, aims to convey scientific knowledge to the scientific community in an objective, neutral, precise, and unambiguous manner. Consequently, authors strive to distance themselves from their text, focusing on the research itself and eliminating redundant elements without clear purpose. In French, these requirements can be met through the specific use of personal pronouns, passive constructions, impersonal verbs/structures, tenses, moods, sentence modes, participial and infinitival forms, nominalizations, and relative clauses. Given the growing volume of scientific papers and journals, researchers face the challenge of presenting their research concisely to capture the reader’s interest. In this context, the abstract plays a crucial role. Universally recognized in scientific circles as an essential component of a research paper, the abstract follows a structured format and succinctly summarizes the article’s main content, making it a distinct genre. Building on these linguistic principles, this mini pilot study examines the elements and structures that ensure neutrality and linguistic economy in French abstracts within the humanities, social, and biomedical sciences, aiming to determine their frequency, reasons for their presence or absence, and the need for further research in this area. The study hypothesized that the occurrence and frequency of the examined linguistic tools would be significant, and that the abstracts would structurally align with the technical requirements set by journals. The results revealed the presence of elements ensuring objectivity and linguistic economy, though their distribution was uneven. Notably, pronouns like on and the authorial we were absent, and the use of impersonal verbs, constructions, and gerunds was minimal. Abstracts predominantly featured forms that promote conciseness (e.g., anaphoric use of personal pronouns, present participles replacing relative clauses, passive constructions without an expressed agent or auxiliary verb). Therefore, the hypothesis that these elements would be widely represented in the corpus was only partially confirmed. Additionally, it can be inferred that the abstracts, as an introduction to a scientific article, is primarily oriented towards concise informativeness. In some abstracts, certain forms appeared more frequently, suggesting that scientific texts are not entirely resistant to the influence of personal style. Thus, the hypothesis that authors strictly follow the guidelines set by scientific journals was not proven. While the findings are limited by the small corpus size, they underscore the relevance of further research in this area.